KELAYAKAN FINANSIAL LAYANAN OJEK DI KABUPATEN WONOGIRI JAWA TENGAH - Handayani, Dewi; Ariyani Soemitro, Ria Asih; Budisatrya Mochtar, Indrasurya; Riyanto, Bambang (Jurnal Transportasi, 2011)
Ojek (motorcycle paratransit) is one form of paratransit in Indonesia, using a motorcycle rented by a person and gives the person a lift. By evaluating the feasibility of ojek services, the sustainability of ojek as a mode of transportation in a rural area can be determined. This research was conducted on ojek services in Wonogiri, Central Java Province. The results indicate that the investment of ojek services for rural areas is feasible to be implemented because it meets the feasibility criteria used in the analysis. The prospect of the existence of ojek in the rural areas in the future is also quite good and is expected to take place for long time, especially in areas with limited formal employment, relatively low education level of job seekers, and low-wage workers.Keywords: paratransit, ojek, rural transportation, feasibility analysis.